Valor nutricional e fracionamento de proteína e carboidratos de silagem pré-secada de capim Tifton 85 com diferentes camadas de filme de polietileno e tempos de armazenamento - Scheidt, Kácia Carine (2016)
The study aimed to assess the nutritional value and quantify the protein fractions and carbohydrates of pre-dried silage Tifton 85 bermudagrass (Cynodon spp cv. Tifton 85) made in the form of bales with capacity of 400 kg, involved in different layers of polyethylene film (stretch), milk white, 25 mm thick, at the time of baling during and 30, 60 and 90 days of storage. The experiment was conducted in municipality of Marechal Cândido Rondon-PR, during the period from November/2014 to February/ 2015. The experimental design was completely randomized with split plot in time, where number of polyethylene film layers (two and three) involving the burdens of pre-dried silage constituted the plots and the evaluation periods (baling, 30, 60 and 90 days of storage) the subplots, with four repetitions. It was found that the contents of dry matter (DM), mineral matter (MM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), cellulose, hemicellulose, lignin, protein insoluble acid detergent (ADIP), in vitro digestibility of dry matter (IVDMD) and in vitro digestibility of the cell wall (IVDCW), were similar (P>0.05) in silages involved with two and three layers of polyethylene film.The protein insoluble in a neutral detergent (NDIP) was higher by 6.01 g / kg CP involved in the silages with two layers of polyethylene film. There was effect (p<0.05) of periods of evaluation of the ADF, NDF, MM, NDIP, cellulose, lignin and IVDMD noting up linear additions to the levels of ADF, cellulose and lignina, and quadratic effect for in MM content, NDIP and NDF and linear decreases to IVDMD content.The DM content (550.3 g/kg), CP (102.27 g/kg DM), ADIP (28.98 g/kg DM), hemicellulose (304.3 g/kg DM) and IVDMD (582.1 g/kg DM) they were not affected by periods of evaluation. There was no difference (P>0.05) for the pre-dried silage involved with two three layers of polyethylene film, for both the protein fractions, such as carbohydrates. There was no effect (p>0.05) the periods of evaluation on the content of TC. There was an increase and a linear decrease (P<0.05) for fractions A + B1 (rapid rumen carbohydrates) and B2 (digestible cell wall carbohydrates),respectively, according to the evaluation periods, presenting decrease of 28.29% TC to 23.22% TC for fractions a + B1 and increase of 65.05% CT to 69.59% CT for B2 fractions. The fraction C (carbohydrates nondigestible in the rumem) presented a quadractricaly (P<0.05), according to the evaluation periods, with an estimated minimum value of 5.54% CT with 24.20 days of storage. For CP, it was observed that the fractions A (non-protein nitrogen) and B1 (soluble protein rapid degradability in the rumen) did not they differed (P>0.05) between the evaluation periods, it is estimated average values 22.75% CP and 7.90% CP, respectively. The B2 fractions (insoluble protein with intermediate degradation rate) and B3 (protein with slow degradation rate) presented quadratic behavior (P<0.05), according to the evaluation periods, estimating maximum value of 37.41% CP with 47.44 days of storage and minimum value of 7.18% CP to 52.53 days of storage, respectively. The fraction C (indigestible protein) presented linear increase of 22.38% CP the 27.79% CP. The number of layers of polyethylene film (stretch) milky white, 25 mm thick, did not affect the nutritional value as well as the carbohydrate and protein fractions of pre-dried silage. The storage can cause changes in the nutritional quality of pre-dried silage, especially in fiber content, IVDMD and the indigestible fractions of protein and carbohydrates